Hittite studies in honor of Harry A. Hoffner Jr. : on the occasion of his 65th birthday - Hoffner, Harry A., Jr., 1934-2015; Beckman, Gary M.; Beal, Richard Henry, 1953-; McMahon, John Gregory, 1953- (Eisenbrauns, 2003)
Annotation.